THE EFFECT OF MITOMYCIN C ON SOME IMMUNOLOGICAL AND CYTOGENETICAL PARAMETERS IN ALBINO MALE MICE - Al-Dahiri, Lamees Kh I (Al-Nahrain Journal of Science, 2009)
The present study was carried out to shed light on the effect of Mitomycin C on some immunological and cytogenetical parameters in albino male mice. The effects of the drugs were investigated after one day treatment with a single dose(0.005 mg/ml). All treatments were paralleled by controls. The results revaled that the dose of MMC significantly decreased the total count of leucocytes, lymphocytes and neutrophils, while the monocytes and eosinophils showed no significant differences, as compared to controls.Such observation was positively correlated with the phagocytic index and plague forming cells. Moreover, the mitotic index showed significantly decreased, as compared with controls. In contrast, the spontaneous formation of micronuclei and chromosomal aberration in the bone marrow cell was significantly increased. The results showed that the MMC had immune suppressive effect. Also, the genotoxicand mutgenic effects was observed